1999
DOI: 10.1021/ja9909024
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 3hJNC and Hydrogen Bond Length in Proteins

Abstract: Establishing a quantitative relationship between backbone-backbone hydrogen-bond (H-bond) length observed in protein crystal structures and recently observed 3h J NC′ couplings across such bonds is limited by the coordinate precision of the X-ray structure. For an immunoglobulin binding domain of streptococcal protein G, very high-resolution X-ray structures are available. It is demonstrated that over the small range of N-O H-bond lengths (2.8-3.3 Å) for which 3h J NC′ couplings are observable, the 32 measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
223
3
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(263 citation statements)
references
References 36 publications
18
223
3
1
Order By: Relevance
“…6D) Fig. 6, changes in trans-hydrogen bond couplings can be evaluated in terms of changes in hydrogen bond distances (17). Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…6D) Fig. 6, changes in trans-hydrogen bond couplings can be evaluated in terms of changes in hydrogen bond distances (17). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Regions of high mobility include loop 43 along with the C-terminal end of strand III and the N-terminal end of strand II and also regions of the disordered loop (residues 13,[17][18] including the start of the ␣-helix (residue 19). In the terminal regions, residues 4 and 54 exhibit high mobility, as well as residue 53 in the R33A and D50A variants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[29 -41] Bax et al determined that 3h J NC is negative and also found an exponential relationship between 3h J NC and R NO (or d N· · ·O , in Å, from X-ray structures): 3h J NC = −59 000 exp(−4R NO ) ±0.09 Hz. [31] Li et al have studied pressure effects on protein G (from 30 to 2000 bar) on 3h J NC ; [32] since the previous equation related 3h J NC and R NO , the difference in coupling constants suggest a compaction of the helix ends and an increase of the helix pitch.…”
Section: Proteins (Ubiquitin Protein G and Others)mentioning
confidence: 99%